Desenvolvimento de metodologia para identificação de oportunidades de inovação tecnológica em tratamento de superfícies de jóias folheadas - Spinola, Adriana Tahereh Pereira (Universidade Federal de São Carlos, 2006)
Technological innovation has been greatly discussed worldwide for its central role in economy. One important factor to innovation is the identification of technological opportunities. Information on customer requirements is particularly important on identifying new opportunities for it leads to a much safer way to new product launch success. In this context, the objective of the present study is to develop and to apply a methodology capable of identifying technological innovation opportunities focused on customer s needs. This methodology has used a well known product development technique called Quality Function Development (QFD) as one of the analytical tools of Competitive Intelligence (CI). Other analytical tools used were: Industry analysis, SWOT and patent analysis. The developed CI cycle based methodology was then applied in Eletrochemical, one of the enterprises of the cluster established in Limeira city, which is the greatest South American producer and exporter of plated jewellery. The innovation opportunities identification focused on surface treatment technologies, taken as one of the key technologies of that Industrial Agglomerate. The results showed a tendency for cleaner processes usage within surface treatment sector that can be applied in plated jewellery. From these emerge technologies such as Physical Vapor Deposition (PVD), nanotechnology based process, or even galvanization baths that substitute cyanide or metals for nickel solutions. The identified technologies and complementary information not only built up the basis of a technological follow up but also guided Eletrochemical decision on planning an internal R&D department. The results proved the proposed methodology capacity to identifying potential technological innovation, as well as its strategic relevance as a basis for decision on R&D and technological management.
Development of a methodology for identyfing technological innovation opportunities in plated jewellery surface treatment
Keywords: Metais; Inteligência competitiva; Desdobramento da função qualidade; Inovações tecnológicas; Jóias folheadas; Galvanização; ENGENHARIAS::ENGENHARIA DE MATERIAIS E METALURGICA